The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20546/ijcmas.2019.805.167
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Sero-epidemiological Study of Leptospirosis in Cattle of Nagpur and Surrounding Regions

Abstract: A zoonotic disease Leptospirosis is caused by pathogen of the genus Leptospira and it is an emerging global public health problem. In the present study a total of 266 cattle blood and sera samples were collected from the towns and villages of Nagpur, Wardha, Bhandara Gadchiroli and Durg districts during December 2017 to 2018 and tested for the presence of Leptospira. These samples were from randomly selected herds with history of repeated breeding, abortion, reproductive disorders, etc. also including some app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…This result was in agreement with the findings of Odontsetseg et al [ 20 ] (23.50%) in Mongolia, Schoonman and Swai [ 21 ] (30.30%) in Tanzania, Gamage et al [ 22 ] (20.30%) in Sri Lanka and Subharat et al [ 23 ] (27.4%) in Australia. Similarly, the present finding was in congruence with results of previous studies by Taddei et al [ 24 ] (19.30%) in unvaccinated animals of Colombian dairy farm, Ismail et al [ 25 ] (26.25%) in Jordan, Tabatabaeizadeh et al [ 26 ] (19.10%) in Iran, Ngbede et al [ 27 ] (25% and 23.90%) in different dairy farms of Zaria (Nigeria), Balamurugan et al [ 28 ] (23.68%) in Chhattisgarh of India, Ismail et al [ 25 ] (28.75%) in Jordan and Shilpa et al [ 29 ] (19.92%) in Nagpur of Indian dairy farms.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with the findings of Odontsetseg et al [ 20 ] (23.50%) in Mongolia, Schoonman and Swai [ 21 ] (30.30%) in Tanzania, Gamage et al [ 22 ] (20.30%) in Sri Lanka and Subharat et al [ 23 ] (27.4%) in Australia. Similarly, the present finding was in congruence with results of previous studies by Taddei et al [ 24 ] (19.30%) in unvaccinated animals of Colombian dairy farm, Ismail et al [ 25 ] (26.25%) in Jordan, Tabatabaeizadeh et al [ 26 ] (19.10%) in Iran, Ngbede et al [ 27 ] (25% and 23.90%) in different dairy farms of Zaria (Nigeria), Balamurugan et al [ 28 ] (23.68%) in Chhattisgarh of India, Ismail et al [ 25 ] (28.75%) in Jordan and Shilpa et al [ 29 ] (19.92%) in Nagpur of Indian dairy farms.…”
Section: Discussionmentioning
confidence: 99%
“…In Alappuzha district of Kerala, Sreekutty et al (2020) reported that the predominant serovars obtained in cattle were Grippotyphosa, Sejroe and Autumnalis. The predominant serovars detected in cattle were serovar Pomona, Hebdomadis, Javanica, Icterohaemorrhagiae and Sejroe by Moon et al (2019), in Nagpur. Soman (2004) reported that the predominant serovars among cattle in Thrissur district, Kerala were Sejroe, Potac and Pomona.…”
Section: Resultsmentioning
confidence: 99%